Survey of intestinal parasites in swine farms raised in Western Nepal - Barshat Chaudhary; Rajendra Prasad Parajuli; Pitambar Dhakal (Veterinary Medicine and Science, 2023)
Abstract Background Pigs (Sus scrofa domesticus), an important domestic livestock, are generally affected by helminth and protozoan parasites. Rearing pigs in rural regions in Nepal is a common practice for subsistence farming. A cross‐sectional survey was conducted to determine the occurrence of gastrointestinal parasites (GIPs) in pigs raised in Western Nepal. Methods A total of 200 faecal samples from commercial and smallholder farms were examined by wet mounts, flotation, sedimentation and staining techniques. Results The results revealed that overall 86.5% of samples were found shedding oocysts or eggs of one or more GIPs. Three species of protozoa [Eimeria sp. (26%), Entamoeba coli (25.5%) and Coccidia (29%)] and nine species of helminths parasites (Ascaris suum (32.5%), Trichuris suis (30%), strongyle‐type nematode (27.5%), hookworm (26%), Fasciola sp. (17.5%), Physaloptera sp. (17.5%), Strongyloides sp. (17.5%), Metastrongylus sp. (8%) and Oesophagostomum sp. (5.5%)] were identified. Female pigs were found to have higher protozoan infection than males, but such a difference was not noticed with regard to helminth parasites. Strongyles and Oesophagostomum infection were higher in commercial farms compared to smallholder farms, whereas the prevalences of E. coli and other protozoans were higher in smallholder farms. Among the contextual factors evaluated for association, weight and gender of pigs, and annual income and gender of managers/caretakers were significantly (p < 0.05) associated with the prevalence of GIPs in pigs. The overall prevalence of certain helminths such as strongyle‐type nematode and A. suum was significantly (p < 0.05) associated with the weight of pigs after adjusting other contextual factors. Conclusions This study detected relatively high prevalence of intestinal parasites in domestic pig facilities. Molecular epidemiological studies are essential to verify the exact zoonotic potential of parasites carried by pigs in the region. An effective periodic monitoring of GIPs of pigs needs to be carried out to minimize their further dissemination.